2009
DOI: 10.1007/s11274-009-0265-2
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of antimicrobial susceptibility profiles and genotyping of Salmonella enterica isolates from clinical cases of salmonellosis in New Mexico in 2008

Abstract: In this study, we investigated the antimicrobial susceptibility profiles and the distribution of some well known genetic determinants of virulence in clinical isolates of Salmonella enterica from New Mexico. The minimum inhibitory concentrations (MICs) for various antimicrobials were determined by using the E-test strip method according to CLSI guidelines. Virulence genotyping was performed by polymerase chain reaction (PCR) using primers specific for known virulence genes of Salmonella enterica. Of 15 isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
1
16
0
2
Order By: Relevance
“…More isolates from different parts of the world and from different origins need to be tested to confirm that the ST543 sequence type was a major worldwide clone based on MLST analysis. Several PCR-based procedures for the detection of known DNA sequences, including virulence genes, have been successfully applied for many Salmonella serovars [15,25,[28][29][45][46]. The main advantages of these approaches were the simplicity, rapidity, and cost effectiveness, which means that many strains could be easily virulotyped [15,32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More isolates from different parts of the world and from different origins need to be tested to confirm that the ST543 sequence type was a major worldwide clone based on MLST analysis. Several PCR-based procedures for the detection of known DNA sequences, including virulence genes, have been successfully applied for many Salmonella serovars [15,25,[28][29][45][46]. The main advantages of these approaches were the simplicity, rapidity, and cost effectiveness, which means that many strains could be easily virulotyped [15,32] .…”
Section: Discussionmentioning
confidence: 99%
“…Virulence genes have been screened using simple [25] or multiplex PCR [26] to determine the distribution of these genes among Salmonella enterica strains [25,27] and to genotype many Salmonella serovars [15,[28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The primers used in this study to amplify the fimbrial genes are listed in Table S1 in the supplemental material. PCR amplification of bcfD, csgA, fimA, lpfD, pefA, safC, sefA, stbD, stfH, sthE, stiH, stjA, and tcfA was performed as described previously (10,(15)(16)(17)(18)(19). PCR primers to amplify the pegD, staA, stcA, stdB, steB, stgA, and stkA genes were established and validated in this study, and the gene accession numbers for the fimbrial genes are shown in Table S1 DNA extraction and PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation between the use of antibiotics and the emergence of resistance has been documented. Moreover, the increasing rate of antibiotic resistance has been reported from 1993 (Threfall et al, 1993) until recently (Smith et al, 2002;Maripandi and Al-Salamah, 2010;Melendez et al, 2010). A variety of antibiotics such as ampicillins, tetracyclines, sulfonamides and streptomycin, have been used for the treatment of salmonellosis leading to the emergence of resistant or multi-resistant strains (Glynn et al, 1998;Metzer et al, 1998;Buyd Περίληψη.…”
mentioning
confidence: 99%
“…The presence of sopE gene has been associated with many Salmonella species such as S. typhimurium, S.typhi, S.enteritidis, S.dublin, S.hadar, S. gallinarum and it is associated with epidemic disease in both humans and animals (Hopkins and Threlfall, 2004;Rahman et al, 2004;Smith et al, 2010;Dione et al, 2011). In present study the great majority of the isolates (34/36 or 97.2%) harbored the sopE gene.…”
mentioning
confidence: 99%